A catalyst for preparing styrene by dehydrogenation of ethylbenzene, a preparation method and application thereof
Patent Information
- Application Number
- CN202211306068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-24
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-10-24
AI Technical Summary
[0008]针对现有乙苯脱氢技术中存在的催化剂在低水比条件下活性较低和稳定性较差的问题,本发明提供一种新的乙苯脱氢制苯乙烯的催化剂及其制备方法和应用
[0034]根据本发明,所述脱氢反应的温度为550~640℃。
Smart Images

Figure CN117920243B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ethylbenzene dehydrogenation, specifically relating to a catalyst for the dehydrogenation of ethylbenzene with a low water ratio to styrene, its preparation method, and its application. Background Technology
[0002] Styrene is a crucial raw material for the synthetic rubber and plastics industries, playing a vital role in the national economy. Due to its wide range of applications, the global styrene industry has developed rapidly, with global styrene production capacity reaching 37 million tons in 2020 and 39.92 million tons in 2021. In recent years, China's styrene production capacity has expanded rapidly, reaching 12.04 million tons in 2020, ranking first in the world. In 2021, China's total styrene production capacity reached 15.362 million tons, with an output of 12.1688 million tons, but this still could not meet the rapidly growing market demand, resulting in imports of 1.69 million tons of styrene. Many companies are building or expanding styrene plants, and the new capacity is expected to reach 6.17 million tons per year in 2022.
[0003] Currently, there are two main methods in the world for producing styrene from ethylbenzene: one is the catalytic dehydrogenation of ethylbenzene to produce hydrogen and styrene. The catalytic dehydrogenation of ethylbenzene has always been the dominant technology for styrene production, accounting for about 85% of the total styrene production capacity. The other is the PO / SM co-oxidation co-production method, which can simultaneously obtain two important basic organic raw materials and has developed rapidly in recent years.
[0004] Ethylbenzene dehydrogenation is a strongly endothermic and reversible reaction involving an increase in the number of molecules, favored by high temperature and low pressure. Industrially, large amounts of high-temperature steam are typically introduced to promote the formation of the target product, styrene. Steam plays a crucial role in the reaction. However, using large amounts of superheated steam as the dehydrogenation medium results in high energy consumption, large product condensation, high equipment costs, and high production costs. Therefore, the ethylbenzene dehydrogenation process aims to achieve a high styrene yield with a low water ratio (the mass ratio of steam to ethylbenzene in the feed). Adopting a low water ratio operation is a key measure for energy conservation and cost reduction. Developing styrene catalysts suitable for low water ratios and improving their activity, selectivity, and stability to achieve energy conservation, cost reduction, and lower production costs in styrene plants has become an urgent need for styrene enterprises.
[0005] Most existing ethylbenzene dehydrogenation catalysts are Fe-K-Ce based, with Fe-K oxides as the main active components and Ce oxides as the main promoters. They also contain other metal oxides as structural stabilizers or electronic promoters. Currently disclosed low-water-ratio ethylbenzene dehydrogenation catalysts mainly improve their activity and stability under low-water-ratio conditions by enhancing catalyst structural stability and modifying catalyst surface properties.
[0006] CN106582692A discloses an ethylbenzene dehydrogenation catalyst in which lead oxide and at least one selected from Er₂O₃, Tm₂O₃, or Yb₂O₃ are added to an iron-potassium-cerium-tungsten-calcium catalytic system, thereby improving the catalyst's activity under low water ratio conditions. CN101279269A discloses a catalyst in which bismuth oxide and beryllium oxide are added to an iron-potassium-cerium-tungsten-calcium catalytic system, thereby improving the stability and activity of the ethylbenzene dehydrogenation catalyst under low water ratio conditions.
[0007] The catalysts reported above exhibited varying degrees of low activity and insufficient stability in the ethylbenzene dehydrogenation reaction under low water ratio conditions. Current styrene production technology is trending towards energy conservation and low carbon emissions. Developing a more active and stable ethylbenzene dehydrogenation catalyst suitable for operation under low water ratio conditions has been a continuous research focus. Summary of the Invention
[0008] To address the problems of low activity and poor stability of catalysts in existing ethylbenzene dehydrogenation technologies under low water ratio conditions, this invention provides a novel catalyst for the dehydrogenation of ethylbenzene to styrene, its preparation method, and its applications. This catalyst exhibits high activity, styrene selectivity, and stability in the ethylbenzene dehydrogenation reaction under low water ratio conditions.
[0009] The first aspect of this invention provides a catalyst for the dehydrogenation of ethylbenzene to styrene, said catalyst comprising oxides of Fe₂O₃, K₂O, CeO₂, MoO₃, CaO, Na₂O, and RE, wherein RE comprises at least one selected from Sm, Eu, Gd, and Tb; and the CeO₂ lattice constant is [missing value].
[0010] According to the present invention, preferably, the CeO2 lattice constant in the catalyst is .
[0011] According to the present invention, the catalyst, based on the total mass of the catalyst, comprises the following components by mass fraction:
[0012] (a) 60%–84% Fe2O3;
[0013] (b) 8%–17% K₂O;
[0014] (c) 4%–11% CeO2;
[0015] (d) 0.5%–5% MoO3;
[0016] (e) 0.1%–4% CaO;
[0017] (f) 0.12–2% Na₂O;
[0018] (g) 0.08% to 3% of the oxides of RE.
[0019] According to the present invention, preferably, RE includes at least one selected from Sm and Gd.
[0020] According to the present invention, preferably, the mass ratio of the oxide of RE to CeO2 is 2 to 25:100, more preferably 2 to 8:100. As a non-limiting example, the specific value of the mass ratio of the oxide of RE to CeO2 can be 3, 4, 5, 6, 7, 9, 10, 12, 14, 16, 18, 20, 22, or 24.
[0021] According to the present invention, preferably, RE simultaneously comprises Sm and Gd. More preferably, the weight ratio of Sm to Gd, based on oxides, is 0.2 to 2:1, more preferably 0.2 to 0.6:1. As a non-limiting example, the specific values of the weight ratio of Sm to Gd can be 0.3, 0.4, 0.5, 0.7, 0.8, 0.9, 1.1, 1.2, 1.4, 1.6, or 1.8. Sm and Gd have a synergistic effect, improving the activity, styrene selectivity, and stability of the catalyst in the ethylbenzene dehydrogenation reaction at low water ratios.
[0022] A second aspect of this invention provides a method for preparing the catalyst for the dehydrogenation of ethylbenzene to styrene, comprising the following steps:
[0023] The catalyst is obtained by uniformly mixing Fe source, K source, Ce source, Mo source, Ca source, Na source, RE source, and optional porogen, kneading and calcining.
[0024] According to the present invention, no binder is added during the preparation process.
[0025] According to the present invention, an appropriate amount of water can be added during the kneading process. The water is added slowly, and the amount is not particularly limited and can be adjusted according to the dryness or wetness of the material. Generally, the amount of water added accounts for 15% to 35% of the mass of the Fe source, K source, Ce source, Mo source, Ca source, Na source, RE source, and optional pore-forming agent. The Fe source, K source, Ce source, Mo source, Ca source, Na source, and RE source are all calculated as oxides.
[0026] According to the present invention, the molding can be carried out by extrusion molding, and the strip can be a particle with a diameter of 2 to 5 mm and a length of 3 to 10 mm.
[0027] According to the present invention, the calcination conditions are as follows: the calcination temperature is 750-1050℃, and the calcination time is 0.5-8h.
[0028] According to the present invention, the shaped material may undergo a drying step before calcination. The drying temperature is 30–200°C, and the drying time is 1–24 hours.
[0029] According to the present invention, the Fe source is added in the form of Fe₂O₃ oxide. The Fe source is preferably selected from iron oxide red and / or iron oxide yellow, more preferably a combination of iron oxide red and iron oxide yellow. The K source is added in the form of a potassium salt; the potassium salt is selected from any one or more of potassium carbonate, potassium nitrate, and potassium bicarbonate. The Ce source is added in the form of a cerium salt; the cerium salt is any one or more of cerium nitrate, cerium oxalate, and cerium carbonate. Preferably, the particle size of the cerium salt is in the range of 0.1-100 μm. The Mo source is added in the form of a molybdenum salt or oxide, wherein the molybdenum salt is ammonium molybdate. The Ca source is added in the form of an oxide, hydroxide, or carbonate. The Na source is added in the form of a sodium salt, wherein the sodium salt is a nitrate or carbonate. The RE source is added in the form of a nitrate or chloride. The pore-forming agent is any one or more of activated carbon, graphite, sodium carboxymethyl cellulose, and polystyrene microspheres. The amount of the pore-forming agent added is 0.01% to 5% of the mass of the Fe source, K source, Ce source, Mo source, Ca source, Na source, and RE source. Among them, Fe source, K source, Ce source, Mo source, Ca source, Na source and RE source are all calculated as oxides.
[0030] The third aspect of the present invention provides the application of the above-described catalyst or the catalyst prepared by the above-described method in the dehydrogenation of ethylbenzene to styrene.
[0031] According to the present invention, the method of application is as follows: the ethylbenzene-containing raw material is contacted with the catalyst of the present invention in the presence of water vapor to carry out a dehydrogenation reaction, thereby obtaining a styrene-containing product.
[0032] According to the present invention, the application of the ethylbenzene dehydrogenation catalyst in the preparation of styrene is suitable for ethylbenzene dehydrogenation at a low water ratio; the low water ratio is 1.15 or less, preferably 0.7 to 1.1. The low water ratio is a weight ratio.
[0033] According to the present invention, water is preheated into steam and fully mixed with the feed gas before entering the reactor.
[0034] According to the present invention, the temperature of the dehydrogenation reaction is 550–640°C.
[0035] According to the present invention, the pressure of the dehydrogenation reaction is an absolute pressure, 20-100 kPa.
[0036] According to the present invention, the mass hourly space velocity (MSV) of ethylbenzene is 0.2–2.0 h⁻¹. -1 .
[0037] Compared with the prior art, the present invention has significant advantages and outstanding effects, as follows:
[0038] 1. In this invention, the inventors discovered through research that CeO2 is an important promoter in Fe-K based ethylbenzene dehydrogenation catalysts, and the catalyst's reactivity and stability are correlated with the lattice constant of CeO2 in the catalyst. Typically, the lattice constant of undoped CeO2 is... RE element doping primarily enters the crystal structure of CeO2 in the catalyst, altering its crystal structure. Further research by the inventors revealed that adding appropriate amounts of Sm, Eu, Gd, and Tb promoters to the catalyst, particularly the simultaneous addition of Sm and Gd within a specific ratio range while controlling their proportion with Ce, can effectively change the grain structure of CeO2, significantly increasing its lattice constant, even if the CeO2 lattice constant is within a certain range. Within a certain range, the catalytic activity of oxygen on the CeO2 surface can be altered, thereby significantly improving the catalytic performance of the catalyst at low water ratios and giving the catalyst good stability.
[0039] In this invention, the inventors selected at least one of the following additives: Sm, Eu, Gd, and Tb. This not only helps to regulate the crystal structure of CeO2, but also improves the selectivity of styrene while enhancing the activity and stability of the catalyst.
[0040] 2. In this invention, the catalyst preparation method involves uniformly mixing Fe source, K source, Ce source, Mo source, Ca source, Na source, RE source, and optionally a porogen, followed by kneading, molding, and calcination to obtain the catalyst. The preparation method specifies that the RE source is a compound containing Sm, Eu, Gd, and Tb, particularly specifying that the RE source is an Sm source and a Gd source, and controlling their ratio with the Ce source. The resulting catalyst has a CeO2 lattice constant within... Within its range, it is suitable for the dehydrogenation of ethylbenzene to prepare styrene under low water ratio conditions, and has high activity, high selectivity and high stability.
[0041] 3. The catalyst of this invention is used in the dehydrogenation reaction of ethylbenzene to styrene. It exhibits high activity, high selectivity and high stability under different water ratios, especially at low water ratios, and has achieved good technical results.
[0042] Using the technical solution of this invention, the catalyst of this invention is evaluated for activity in an isothermal fixed bed at 40 kPa (absolute pressure) and ethylbenzene mass hourly space velocity (MHSV) of 0.5 h⁻¹. -1The catalyst was evaluated at 600℃ under conditions where the water ratio was reduced from the usual 2.0 (by weight) to 0.8 (by weight). After 100 hours of reaction, the ethylbenzene conversion reached 73.6%, and the styrene selectivity reached 97.6%. After 1000 hours of operation, the catalyst showed good stability, with no significant change in styrene selectivity and ethylbenzene conversion. This indicates that the catalyst of this invention, when used in the dehydrogenation of ethylbenzene to styrene, especially under low water ratio conditions, exhibits high activity, styrene selectivity, and stability, achieving good technical results. Detailed Implementation
[0043] The present invention will be further illustrated by the following embodiments, but the scope of protection of the present invention is not limited by the embodiments.
[0044] In this invention, the CeO2 lattice constant is calculated based on the diffraction peak of the CeO2(111) crystal plane in the X-ray diffraction pattern, that is, the diffraction peak corresponding to the position of 2θ=28.50±0.20°.
[0045] XRD was performed using a Rigaku Ultima IV X-ray powder diffractometer from Japan, with a Cu-Kα ray source (λ = 0.15406 nm), a nickel filter, an operating voltage of 35 kV, a current of 25 mA, and a scan rate of 2° / min.
[0046] For the (hkl) crystal plane, the lattice constant a is calculated using the following formula:
[0047]
[0048] In the formula, λ is the X-ray wavelength, θ is the Bragg diffraction angle, and hkl is the crystal plane symbol.
[0049] In this invention, the performance of the catalyst for the ethylbenzene dehydrogenation reaction is evaluated in an isothermal fixed bed. The process is briefly described below:
[0050] The reactor is a 1” stainless steel tube filled with 50–150 mL of catalyst with a diameter of 3–10 mm. Deionized water and ethylbenzene are separately metered into a preheating mixer, preheated and mixed into a gaseous state before entering the reactor. The reactor is heated by an electric heating wire to reach a predetermined temperature. The reactants flowing out of the reactor are condensed in water and their composition is analyzed by gas chromatography.
[0051] Ethylbenzene conversion and styrene selectivity are calculated using the following formulas:
[0052]
[0053]
[0054] Styrene yield % = Ethylbenzene conversion % * Styrene selectivity %.
[0055]
Example 1
[0056] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium carbonate (K₂O), 9.2 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium hydroxide (CaO), 1.2 parts of sodium carbonate (Na₂O), 0.2 parts of samarium nitrate (Sm₂O₃), 0.4 parts of gadolinium nitrate (Gd₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0057] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (MSV) of 0.5 h⁻¹ at 40 kPa (absolute pressure). -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0058]
Example 2
[0059] Weigh out the following amounts: 40.2 parts of iron oxide red (Fe₂O₃), 21.5 parts of iron oxide yellow (Fe₂O₃), 16.8 parts of potassium carbonate (K₂O), 10.6 parts of cerium carbonate (CeO₂) (particle size range of 0.1-100 μm), 4.5 parts of ammonium molybdate (MoO₃), 3.9 parts of calcium hydroxide (CaO), 1.9 parts of sodium carbonate (Na₂O), 0.12 parts of samarium nitrate (Sm₂O₃), 0.48 parts of gadolinium nitrate (Gd₂O₃), and 2.2 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add 15% (by weight) of deionized water (based on the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 50 °C for 20 h and 160 °C for 4 h. Finally, they were placed in a muffle furnace and calcined at 800 °C for 6 h to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0060] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (MSV) of 0.5 h⁻¹ at 40 kPa (absolute pressure).-1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1.
[0061]
Example 3
[0062] Weigh out the following amounts: 35.6 parts of iron oxide red (Fe₂O₃), 34.6 parts of iron oxide yellow (Fe₂O₃), 10.6 parts of potassium carbonate (K₂O), 10.9 parts of cerium carbonate (CeO₂) (particle size range of 0.1-100 μm), 4.8 parts of ammonium molybdate (MoO₃), 1.8 parts of calcium hydroxide (CaO), 1.4 parts of sodium carbonate (Na₂O), 0.1 parts of samarium nitrate (Sm₂O₃), 0.2 parts of gadolinium nitrate (Gd₂O₃), and 0.01 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (32% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. Next, the above mixture was extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 200 °C for 1 h. Finally, they were placed in a muffle furnace and calcined at 1000 °C for 2 h to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0063] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (MSV) of 0.5 h⁻¹ at 40 kPa (absolute pressure). -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0064]
Example 4
[0065] Weigh out the following amounts: 45.2 parts of iron oxide red (Fe₂O₃), 38.4 parts of iron oxide yellow (Fe₂O₃), 8.2 parts of potassium carbonate (K₂O), 6.8 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 0.5 parts of ammonium molybdate (MoO₃), 0.2 parts of calcium hydroxide (CaO), 0.4 parts of sodium carbonate (Na₂O), 0.1 parts of samarium nitrate (Sm₂O₃), 0.2 parts of gadolinium nitrate (Gd₂O₃), and 4.6 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add 24% (by weight) of deionized water (based on the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0066] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0067]
Example 5
[0068] Weigh out the following amounts: 50.3 parts of iron oxide red (Fe₂O₃), 27.5 parts of iron oxide yellow (Fe₂O₃), 10.3 parts of potassium carbonate (K₂O), 6.45 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 1.6 parts of ammonium molybdate (MoO₃), 3.5 parts of calcium hydroxide (CaO), 0.2 parts of sodium carbonate (Na₂O), 0.05 parts of samarium nitrate (Sm₂O₃), 0.1 parts of gadolinium nitrate (Gd₂O₃), and 2.2 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0069] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1.
[0070]
Example 6
[0071] Weigh out the following amounts: 37.2 parts of iron oxide red (Fe₂O₃), 33.0 parts of iron oxide yellow (Fe₂O₃), 12.3 parts of potassium carbonate (K₂O), 10.6 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 1.5 parts of ammonium molybdate (MoO₃), 3.1 parts of calcium hydroxide (CaO), 1.5 parts of sodium carbonate (Na₂O), 0.3 parts of samarium nitrate (Sm₂O₃), 0.5 parts of gadolinium nitrate (Gd₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0072] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1.
[0073]
Example 7
[0074] Weigh out the following amounts: 46.5 parts of iron oxide red (Fe₂O₃), 24.2 parts of iron oxide yellow (Fe₂O₃), 10.7 parts of potassium carbonate (K₂O), 10.1 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 3.0 parts of ammonium molybdate (MoO₃), 3.1 parts of calcium hydroxide (CaO), 1.8 parts of sodium carbonate (Na₂O), 0.2 parts of samarium nitrate (Sm₂O₃), 0.4 parts of gadolinium nitrate (Gd₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0075] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1.
[0076]
Example 8
[0077] Weigh out the following amounts: 38.6 parts of iron oxide red (Fe₂O₃), 35.6 parts of iron oxide yellow (Fe₂O₃), 12.5 parts of potassium nitrate (K₂O), 4.5 parts of cerium nitrate (CeO₂), 3.6 parts of MoO₃, 3.3 parts of CaO, 1.6 parts of sodium carbonate (Na₂O), 0.1 parts of samarium nitrate (Sm₂O₃), 0.2 parts of gadolinium nitrate (Gd₂O₃), and 1.5 parts of activated carbon. Stir in a mixer for 2 hours until homogeneous. Then add 24% (by weight) of deionized water (based on the total weight of the dehydrogenation catalyst raw materials) and mix for 2 hours. Next, extrude and granulate the mixture to obtain particles with a diameter of 3 mm and a length of 6 mm. Dry these particles in an oven at 80°C for 4 hours, then at 160°C for 4 hours. Finally, calcine them in a muffle furnace at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO₂ in the catalyst are listed in Table 1.
[0078] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1.
[0079]
Example 9
[0080] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium bicarbonate (K₂O), 9.2 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium carbonate (CaO), 1.2 parts of sodium nitrate (Na₂O), 0.5 parts of samarium nitrate (Sm₂O₃), 0.5 parts of gadolinium nitrate (Gd₂O₃), and 1.5 parts of graphite. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0081] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0082]
Example 10
[0083] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium carbonate (K₂O), 9.2 parts of cerium oxalate (CeO₂, particle size range 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium hydroxide (CaO), 1.2 parts of sodium carbonate (Na₂O), 0.6 parts of samarium nitrate (Sm₂O₃), and 1.5 parts of polystyrene microspheres. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0084] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1.
[0085]
Example 11
[0086] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium carbonate (K₂O), 9.2 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium hydroxide (CaO), 1.2 parts of sodium carbonate (Na₂O), 0.6 parts of europium nitrate (Eu₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add 24% (by weight) of deionized water (based on the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0087] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0088]
Example 12
[0089] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium carbonate (K₂O), 9.2 parts of cerium carbonate (CeO₂) (particle size range of 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium hydroxide (CaO), 1.2 parts of sodium carbonate (Na₂O), 0.6 parts of terbium nitrate (Tb₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add 24% (by weight) of deionized water (based on the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0090] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0091] Comparative Example 1
[0092] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium carbonate (K₂O), 9.2 parts of cerium carbonate (CeO₂) (particle size range of 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium hydroxide (CaO), 1.2 parts of sodium carbonate (Na₂O), 0.6 parts of lanthanum nitrate (La₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add 24% (by weight) of deionized water (based on the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0093] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0094] Comparative Example 2
[0095] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium carbonate (K₂O), 9.2 parts of cerium carbonate (CeO₂, particle size range 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium hydroxide (CaO), 1.2 parts of sodium carbonate (Na₂O), 1.5 parts of samarium nitrate (Sm₂O₃), 0.3 parts of gadolinium nitrate (Gd₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0096] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0097] Comparative Example 3
[0098] Weigh out the following amounts: 46.2 parts of iron oxide red (Fe₂O₃), 25.0 parts of iron oxide yellow (Fe₂O₃), 12.8 parts of potassium carbonate (K₂O), 9.2 parts of cerium carbonate (CeO₂) (particle size range of 0.1-100 μm), 2.8 parts of ammonium molybdate (MoO₃), 2.2 parts of calcium hydroxide (CaO), 1.2 parts of sodium carbonate (Na₂O), 1.5 parts of samarium nitrate (Sm₂O₃), 1.5 parts of gadolinium nitrate (Gd₂O₃), and 1.5 parts of sodium carboxymethyl cellulose. Stir in a mixer for 2 hours until homogeneous. Then add deionized water (24% of the total weight of the dehydrogenation catalyst feedstock) and mix for 2 hours. The mixture was then extruded and granulated to obtain particles with a diameter of 3 mm and a length of 6 mm. These particles were then placed in an oven and dried at 80°C for 4 hours and 160°C for 4 hours. Finally, they were placed in a muffle furnace and calcined at 900°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst and the lattice constant of CeO2 in the catalyst are listed in Table 1.
[0099] 100 mL of dehydrogenation catalyst was loaded into the reactor and subjected to an ethylbenzene mass hourly space velocity (H₂O) of 40 kPa (absolute pressure) and 0.5 h⁻¹. -1 The performance was evaluated under the conditions of reaction temperature 600℃ and water ratio 0.8 (wt). The test results after 100h of reaction are listed in Table 1, and the test results after 1000h of reaction are listed in Table 2.
[0100] Table 1. Catalyst composition, properties, and evaluation results for the examples and comparative examples.
[0101]
[0102]
[0103] *Contains 0.6 parts by weight of La2O3.
[0104] Table 2. Stability evaluation results of dehydrogenation catalysts in the examples and comparative examples.
[0105]
[0106]
[0107] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A catalyst for the dehydrogenation of ethylbenzene to styrene at a low water ratio, said catalyst comprising oxides of Fe2O3, K2O, CeO2, MoO3, CaO, Na2O and RE, wherein the lattice constant of CeO2 is 5.430–5.450 Å; The mass ratio of RE oxide to CeO2 is 2–8:100; RE includes both Sm and Gd; the weight ratio of Sm and Gd, as oxides, is 0.2 to 0.6:
1.
2. The catalyst according to claim 1, characterized in that, The catalyst, based on its total mass, comprises the following components by mass fraction: (a) 60%–84% Fe2O3; (b) 8%–17% K₂O; (c) 4%–11% CeO2; (d) 0.5%–5% MoO3; (e) 0.1%–4% CaO; (f) 0.12–2% Na₂O; (g) 0.08% to 3% of the oxides of RE.
3. A method for preparing the catalyst according to any one of claims 1 to 2, comprising the following steps: The catalyst is obtained by uniformly mixing Fe source, K source, Ce source, Mo source, Ca source, Na source, RE source, and optional porogen, kneading and calcining.
4. The preparation method according to claim 3, characterized in that, The Fe source was added in the form of Fe2O3 oxide; And / or, the K source is added in the form of a potassium salt; the potassium salt is selected from any one or more of potassium carbonate, potassium nitrate, and potassium bicarbonate; And / or, the Ce source is added in the form of a cerium salt; the cerium salt is any one or more of cerium nitrate, cerium oxalate, and cerium carbonate; And / or, the Mo source is added in the form of a molybdenum salt or oxide; the molybdenum salt is ammonium molybdate; And / or, the Ca source is added in the form of an oxide, hydroxide, or carbonate; And / or, the Na source is added in the form of a sodium salt, wherein the sodium salt is a nitrate or a carbonate; And / or, the RE source is added in the form of nitrate or chloride; And / or, the pore-forming agent is any one or more of activated carbon, graphite, sodium hydroxymethyl cellulose, and polystyrene microspheres.
5. The preparation method according to claim 4, characterized in that, The amount of the porogen added is 0.01% to 5% of the mass of the Fe source, K source, Ce source, Mo source, Ca source, Na source, and RE source; And / or, the Fe source is selected from iron oxide red and / or iron oxide yellow; And / or, the particle size range of the cerium salt is 0.1-100 μm.
6. The application of the catalyst according to any one of claims 1 to 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 5 in the dehydrogenation of ethylbenzene to styrene at a low water ratio.
7. The application according to claim 6, characterized in that, The method of application is as follows: the ethylbenzene-containing raw material is contacted with the catalyst in the presence of water vapor to carry out a dehydrogenation reaction, thereby obtaining a styrene-containing product.
8. The application according to claim 7, characterized in that, The application is suitable for ethylbenzene dehydrogenation under low water-to-acetate ratios; the low water-to-acetate ratio is below 1.15; and / or, the dehydrogenation reaction temperature is 550~640℃; and / or, the dehydrogenation reaction pressure is an absolute pressure of 20~100 kPa; and / or, the ethylbenzene mass hourly space velocity is 0.2~2.0 h⁻¹. -1 .
9. The application according to claim 8, characterized in that, The low water ratio is 0.7~1.1.
Citation Information
Patent Citations
Low water ratio catalyst for preparing phenylethylene from dehydrogenation of phenylethane
CN101279269A
High-activity and low-water-ratio ethylbenzene dehydrogenation catalyst
CN106582692A
Ethylbenzene dehydrogenation catalyst, and preparation method and application thereof
CN103769141A
High-activity and low-water-ratio ethylbenzene dehydrogenation catalyst
CN106582678A
Ethylbenzene dehydrogenation catalyst with low vapor to ethylbenzene ratio, and preparation method and application thereof
CN110681393A